Analysis of Social Resilience Conditions and Economic Strength of Farmers After the Covid-19 Pandemic in the Coastal Area - Hotden Leonardo Nainggolan; Albina Ginting; Susana Tabah Trina (Faculty of Animal and Agricultural Science, Diponegoro University, 2025)
This study aims to determine the condition of social resilience and economic strength of farmers after the COVID-19 pandemic in coastal areas. The study was conducted in Deli Serdang Regency. The population of this study were farmers who depended on their economic activities in the agricultural sector affected by the COVID-19 pandemic, namely in Percut Sei Tuan District, totaling 12,178 farmer families. The sample in the study was determined as many as 99 respondents using the Slovin formula. The data used in this study were primary and secondary data and were analyzed descriptively. Based on the results of the study, it was concluded; a) the existing condition of farmers' socio-economic resilience is at high vulnerability, based on the financial capital index with a value of 0.788; farmers seek work outside of farming with a high vulnerability index with a value of 0.758; farmers rely on a loan system with a vulnerability index value of 0.858; b) the existing condition of farmers' economic strength in coastal areas is still very vulnerable with an average indicator of total farmer income of IDR 3,313,744.48/month, lower than the regional minimum wage of IDR3,505,076. Based on the research results, it is recommended that the government empower farmers in the coastal areas of Deli Serdang Regency in a programmed and sustainable manner by optimizing the use of available resources in order to strengthen the social and economic resilience of farmers.